Buffett and beyond : uncovering the secret ratio for superior stock selection - Belmonte, Joseph (Hoboken ; Wiley, 2015)
'Construct a portfolio that is sure to outperform market averagesWarren Buffett had it right all along. Now it's your turn to learn how to construct a portfolio that is sure to outperform the market averages, as well as almost every professional money manager in the world. Warren Buffett's method of predictability can determine a future target price, which in turn determines his all-important purchase price. However, Buffett doesn't draw conclusions of his predictability method relative to the future total returns of portfolios. That's where Buffett and Beyond comes in, taking Buffett's method one giant step beyond, proving that if you select a portfolio of stocks using the predictability method in this book, you will outperform 96% of professional money managers over the long term.In addition to the information in the book, readers will have access to a password-protected website that includes tutorial videos, PowerPoint slides, free trial access to a video newsletter, and a trial subscription to the author's computer program, which follows the research presented in the book. Explains Clean Surplus Accounting (CSA) to determine Return on Owners' Equity (ROE) Uses CSA to determine ROE in a unique way to verify Buffett's all-important purchase price Draws conclusions between Clean Surplus Return on Equity and future total returns Shows that every portfolio selected from the S&P 500 index with above-average Clean Surplus ROEs outperformed the S&P average during the test periods from 1987 to the present If you're an investor, this book will impact your financial life forever'--
Includes index.
Keywords: Buffett, Warren; Investment analysis; Securities